2020
DOI: 10.1186/s13099-020-0345-2
|View full text |Cite
|
Sign up to set email alerts
|

Colistin-resistant Escherichia coli carrying mcr-1 in food, water, hand rinse, and healthy human gut in Bangladesh

Abstract: Background: One of the most significant public health concerns in today's world is the persistent upsurge of infections caused by multidrug resistant bacteria. As a result, clinicians are being forced to intervene with either less effective backup drugs or ones with substantial side-effects. Colistin is a last resort antimicrobial agent for the treatment of infections caused by multi-drug resistant gram-negative bacteria.Methods: Escherichia coli (n = 65) isolated from street food (n = 20), hand rinse (n = 15)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 32 publications
5
27
2
1
Order By: Relevance
“…Regarding the high incidence of erythromycin- and sulphamethoxazole-resistance, the results of the present study are in agreement with those recently reported [ 44 ] on E. coli isolated from different sources. Although several reports on E. coli highlighted a wide distribution of colistin resistance, frequently mediated by the mobile mcr gene [ 44 ], in the present study, the percentage of resistance against colistin was low. This finding is great of interest because colistin is recognized as the last-resort antibiotic for the treatment of infectious diseases caused by multidrug-resistant (MDR) gram-negative bacteria [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Regarding the high incidence of erythromycin- and sulphamethoxazole-resistance, the results of the present study are in agreement with those recently reported [ 44 ] on E. coli isolated from different sources. Although several reports on E. coli highlighted a wide distribution of colistin resistance, frequently mediated by the mobile mcr gene [ 44 ], in the present study, the percentage of resistance against colistin was low. This finding is great of interest because colistin is recognized as the last-resort antibiotic for the treatment of infectious diseases caused by multidrug-resistant (MDR) gram-negative bacteria [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although several reports on E. coli highlighted a wide distribution of colistin resistance, frequently mediated by the mobile mcr gene [ 44 ], in the present study, the percentage of resistance against colistin was low. This finding is great of interest because colistin is recognized as the last-resort antibiotic for the treatment of infectious diseases caused by multidrug-resistant (MDR) gram-negative bacteria [ 44 ]. Moreover, as recommended by the EUCAST subcommittee [ 45 ], in the present study the resistance to colistin was confirmed by determination of MIC through broth micro-dilution method.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The mcr-1 gene is primarily found in E. coli and K. pneumoniae of human origin, which is in line with our study. The plasmid-mediated Col-R possibly developed in animals and was ultimately transmitted to humans [5,32,33]. The four human isolates which harboured mcr-1 in our study were isolated from one septic ICU patient and three patients with urinary tract infections from different wards.…”
Section: Discussionmentioning
confidence: 81%
“…Colistin is a last resort for the treatment of infections caused by MDR gram-negative bacteria ( Johura et al., 2020 ), and in recent years, E. coli strains carrying the mcr-1 gene, which confers resistance to colistin, have become widespread in the poultry industry. In this study, the detection rate was very low; in fact, only 1 farm detected the mcr-1 gene at the early fattening stage.…”
Section: Discussionmentioning
confidence: 99%